2022
DOI: 10.1002/jgc4.1623
|View full text |Cite
|
Sign up to set email alerts
|

Examining the effect of patient personality types and coping styles on outcomes of genetic counseling

Abstract: Both empirical data and genetic counselors' clinical experienceshow that genetic counseling is not equally beneficial to all patients (Thomas & McAllister, 2019). However, there is insufficient research data to accurately identify characteristics of those who benefit more or less from the service. Not only is this important from the perspective of tailoring services to ensure maximum benefit for all patients, but it is also of potential relevance to patient prioritization/ triage decisions. Specifically, deman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Awareness of this personality trait among our counselees might be key to embrace their emotional needs and help them adapt to the genetic test result. A recent study (Salman et al, 2022) showed that genetic counseling increases empowerment, regardless of personality dimensions and coping styles. Our results add some evidence to this topic showing that personality dimensions impact psychological distress after genetic counseling and testing.…”
Section: Discussionmentioning
confidence: 99%
“…Awareness of this personality trait among our counselees might be key to embrace their emotional needs and help them adapt to the genetic test result. A recent study (Salman et al, 2022) showed that genetic counseling increases empowerment, regardless of personality dimensions and coping styles. Our results add some evidence to this topic showing that personality dimensions impact psychological distress after genetic counseling and testing.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive genetic risk assessment could aid in the discussion with these patients regarding empiric risks for cancer for the patient and her relatives given family history and how to communicate this information to them. Studies have shown that genetic counseling increases empowerment, and in cases like these, this type of empowerment can be of tremendous benefit to the patient [16,17].…”
Section: Andandmentioning
confidence: 99%